Workplace experiences of gay and lesbian criminal justice officers in the United States:: a qualitative investigation of officers attending a LGBT law enforcement conference - Mennicke, Annelise (Policing and society, 2018)
Criminal justice culture values traditional masculinity, which has led to adverse workplace experiences for officers who identify as lesbian, gay, bisexual, or transgender (LGBT). This study used focus group data to explore the workplace experiences of 10 law enforcement and 4 corrections officers in the US who attended an LGBT criminal justice conference in 2012. Gay men reported more severe and overt discrimination experiences, while women experienced more covert discrimination. Gay men in the focus groups described engaging in impression management behaviours by acting hypermasculine so as not to raise suspicions about sexual identity and to address presumptions about workplace competency. Additionally, participants believed that homophobia in the work environment created safety concerns for officers working in corrections settings, as participants did not trust that their co-workers would have their back or provide assistance in threatening situations. Conclusions underscore the need to foster supportive and non-discriminatory policies that value contributions across gender identities and expressions.